Climate Change Exacerbated Sexual and Gender-Based Violence: Role of the Feminist Foreign Policy - Mandal, Moumita (Environmental policy and law, 2024)
Feminist foreign policy (FFP) ensures the representation and participation of women both nationally and internationally. Initially, it aimed to focus on some special areas relating to women, peace and security especially sexual violence in conflict and women representation in peace process. Now, the ambit has been broadened and issues relating to climate change are also included. The research has already proved that women suffer double victimization as a consequence of climate change. Climate change exacerbates sexual and gender-based violence (SGBV), so, they face all types of consequences of climate change (CC) and natural disasters as human beings but they face SGBV in particular because of their gender. The FFP states respect for international law and efforts to address gender inequalities and violence. Unfortunately, the existing international law e.g. the CEDAW or human rights treaties etc. generally or law on climate change e.g. the UNFCCC, the Paris Agreement etc. specifically do not address the issue. Also, the interlinkage between climate change and SGBV has not been discussed earnestly. The FFP has been consistently pursued at the UNFCCC COP negotiations in the context of climate peace initiative etc and involved women especially local and indigenous in the decision-making process. Thus, the FFP can be one of the strongest global voices to end SGBV by ensuring women’s participation; addressing the legal gap; and advocating for the adoption of the gender-responsive law and policy both nationally and internationally. They can be a leader at the international level and a change-maker at the national level. This study has sought to explain how climate change exacerbated SGBV has emerged as a subject of FFP and how it can address the challenge of SGBV exacerbated by CC, the relevant legal issues therein and the road ahead.